2013
DOI: 10.1093/ejcts/ezt293
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endarterectomy for chronic thrombo-embolic pulmonary hypertension: an institutional experience†

Abstract: Starting a pulmonary endarterectomy program with acceptable mortality and morbidity rates and satisfactory early-term outcomes increases awareness of the CTEPH and surgery. Preoperative factors can primarily predict postoperative outcome after PEA. Identifying the risk factors in order to achieve a good result is important for the success of a PEA program. Therefore all patients diagnosed with CTEPH should be referred for consideration of PEA in a specialized centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
1
36
2
3
Order By: Relevance
“…Surgical candidates undergo PEA according to the standardized technique previously described. 11 We treated the patient with immunosupressive therapy and inhaler iloprost -a stable analogue of prostacyclin-postoperatively. Following extubation, inhaled iloprost was started at doses of 2.5 µg, six times per day since iloprost is known to reduce residual postoperative PH, decrease right ventricular afterload, and may facilitate the early postoperative management after PEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical candidates undergo PEA according to the standardized technique previously described. 11 We treated the patient with immunosupressive therapy and inhaler iloprost -a stable analogue of prostacyclin-postoperatively. Following extubation, inhaled iloprost was started at doses of 2.5 µg, six times per day since iloprost is known to reduce residual postoperative PH, decrease right ventricular afterload, and may facilitate the early postoperative management after PEA.…”
Section: Discussionmentioning
confidence: 99%
“…Following extubation, inhaled iloprost was started at doses of 2.5 µg, six times per day since iloprost is known to reduce residual postoperative PH, decrease right ventricular afterload, and may facilitate the early postoperative management after PEA. 11 It has been shown that inhaler iloprost was effective in PAH associated with connective tissue diseases and in operable CTEPH. 12 In conclusion, Takayasu's arteritis may mimic CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…8) It is now considered to be a distal vasculopathy, in which structural changes caused by vascular remodeling and inflammation play a major role. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, the pathophysiologic mechanism of increased PVR has not been well clarified so far.…”
Section: Discussionmentioning
confidence: 99%
“…Operative procedure was performed as explained with details in previous article. 14) Shortly, the operation was performed on deep hypothermia (20°C) for both lungs under complete circulatory arrest. A true endarterectomy was accomplished and, when it was completed on both sides, circulation with warming was restarted.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently published our preliminary results (22) . Our operative mortality is now 12% (unpublished data) and was mostly because of patients with persistent pulmonary hypertension after endarterectomy.…”
Section: Ptementioning
confidence: 99%